Empowering Knowledge Societies: The Convergence of Library Science, Digital Innovation, Cultural Preservation, and Sustainable Development in the Modern Information Era - G. S., Maneesh; Vijayan, Sudhi S (Access: An International Journal of Nepal Library Association, 2025)
In the digital age, libraries have become institutions that help people get knowledge, keep cultural heritage alive, improve technology, and support sustainable growth. This piece discusses how libraries help build more powerful knowledge societies. It does this by looking at how library science combines with new digital technologies and cultural preservation to achieve the goals of fairness, sustainability, and inclusion. It talks about how libraries have changed over time, how technologies like AI and blockchain are being used, and how important it is to digitize cultural material to ensure it is available to everyone and lasts a long time. The piece also looks at how libraries help reach the Sustainable Development Goals (SDGs) of the United Nations by providing educational services for everyone and putting in place green infrastructure. Libraries are essential for changing society because they unite different fields and encourage people to work together. The study points out significant problems, such as moral, financial, and physical obstacles, and also suggests clever ways to solve them through new ideas, partnerships, and government actions. The piece ends with suggestions for how to make the knowledge societies of the future better places to live, where libraries are more than places to find information. They are also crucial for digital democracy, cultural continuity, and longterm human growth.